Cephalometric evaluation of Haas and Hyrax rapid maxillary appliances in the treatment of the skeletal maxillary transverse deficiency. - (:unkn) unknown (My University, 1993)
Two different rapid palatal expansion appliances were compared, using lateral cephalograms, anterio-posterior cephalograms and diagnostic models. The Haas appliance was used on ten patients and the Hyrax appliance on another ten. A difference in the effect of the two appliances was found only for the increase in intermolar distance. This difference could be the result of the different appliance design.